Efficacy and Safety of Non-recommended Dose of New Oral Anticoagulants in Patients With Atrial Fibrillation: A Systematic Review and Meta-Analysis - Kong, Xiangyun; Zhu, Yong; Pu, Lianmei; Meng, Shuai; Zhao, Lihan; Zeng, Wei; Sun, Weiyan; Wu, Guangming; Li, Hong (Frontiers in Cardiovascular Medicine, 2021)
Introduction: The real-world treatment of atrial fibrillation (AF) often involves the prescription of new oral anticoagulants (NOACs) using dosing both lower and higher than recommended guidelines. Our study aimed to evaluate the efficacy and safety of non-recommended dosage of NOACs in AF patients. Methods: A systematic search was performed for relevant studies across multiple electronic databases (PubMed, Embase, Cochrane Library, Clinical Trials Registry) from inception to May 1, 2021. Multicenter randomized trials and observational studies were selected with key reporting measures for inclusion involved efficacy outcomes including stroke or systemic thromboembolism along with safety endpoints assessing major or clinically relevant bleeding events. Results: A total of 11 eligible studies were included involving 48,648 patients receiving recommended dose of NOACs and 50,116 patients receiving non-recommended dosage. Compared to AF patients treated with recommended dose regimens, administration of low dose of NOACs was associated with higher risk of stroke/systemic embolism (RR = 1.24, 95% CI 1.14–1.35, P < 0.00001), but without reducing bleeding risk (RR = 1.18, 95% CI 0.91–1.53, P = 0.21) and a higher risk of all-cause mortality (RR = 1.58, 95% CI 1.25–1.99, P = 0.0001). Moreover, high dose of NOACs was associated with higher risk of stroke and systemic embolism efficacy (RR = 1.71, 95% CI 1.06–2.76, P = 0.03) and a non-significant trend to a greater risk of major or clinically relevant bleeding (RR = 1.57, 95% CI 0.96–2.58, P = 0.07). Conclusions: AF patients treated with low dose of NOACs showed equivalent safety but with worse efficacy compared with recommended dose. High dose of NOACs was not superior to recommended dose regimens in preventing stroke/systemic embolism outcomes in AF patients.